Synthesis and Characterization of Silver Nanoparticles Using Cannonball Leaves and Their Cytotoxic Activity against MCF-7 Cell Line - Preetha Devaraj; Prachi Kumari; Chirom Aarti; Arun Renganathan (Journal of Nanotechnology)
Cannonball (Couroupita guianensis) is a tree belonging to the family Lecythidaceae. Various parts of the tree have been reported to contain oils, keto steroids, glycosides, couroupitine, indirubin, isatin, and phenolic substances. We report here the synthesis of silver nanoparticles (AgNPs) using cannonball leaves. Green synthesized nanoparticles have been characterized by UV-Vis spectroscopy, SEM, TEM, and FTIR. Cannonball leaf broth as a reducing agent converts silver ions to AgNPs in a rapid and ecofriendly manner. The UV-Vis spectra gave surface plasmon resonance peak at 434 nm. TEM image shows well-dispersed silver nanoparticles with an average particle size of 28.4 nm. FTIR showed the structure and respective bands of the synthesized nanoparticles and the stretch of bonds. Green synthesized silver nanoparticles by cannonball leaf extract show cytotoxicity to human breast cancer cell line (MCF-7). Overall, this environmentally friendly method of biological silver nanoparticles production provides rates of synthesis faster than or comparable to those of chemical methods and can potentially be used in various human contacting areas such as cosmetics, foods, and medical applications.